Molecular and Cell Biological Considerations in the Initiation and Development of Sporadic Non-Hereditary Solid Cancers - F. Niculescu Vladimir (Journal of Cancer Genetics And Biomarkers, 2018)
This paper reviews the state of cancer research in the post-mutation era. It presents cancer as a highly complex disease viewed differently by scientists from various research fields. Histopathologists considered cancer as a disease of cell differentiation, cancer cell biologists overestimated the causal role of accumulated DNA mutations. More recently molecular biologists have focused on driver genes and driver mutations, regulatory gene networks and deregulation of the genomic balance between unicellular and multicellular gene sets (UG/MG balance). From a developmental biological standpoint, there is a clear analogy between the reproductive life cycles of cancer and protists. The key player of both analogous life cycles is the polyploid cyst, the atavistic cyst-like structure aCLS (PGCC). In the analogy to protists, we assume that the first aCLS initiating cancer originates from a mitoticly blocked cell (cell of origin of cancer, protoprecursor) that escapes death entering an atavistic reproductive process of polyploidisation and depolyploidisation; it forms the atavistic cyst-like structure aCLS and numerous daughter cells (microcells). The microcell progeny develops a multi-lined cell lineage containing stem cells as well as somatic and reproductive cells and clones. Subsequent aCLSs are formed sequentially by committed daughter cells or occasionally by stressed somatic cells. Accordingly, cancer initiation occurs by genomic changes leading to the amitotic cell state and reactivation of an atavistic life cycle. In humans, atavistic life cycles and hyperpolyploidisation (n >16) are mostly repressed by stable gene regulatory networks – but not in cancer. The permanent UG/MG gene conflict and robust ancient surveillance mechanisms trigger a cascade of molecular lesions leading to genomic heterogeneity and aberrant cancer cell states.
Keywords: atavistic theory